AKURASI METODE INSPEKSI VISUAL DENGAN ASAM ASETAT/IVA UNTUK DETEKSI DINI KANKER LEHER RAHIM - Yunita Marliana (poltekkes kemenkes mataram, 2014)
Abstract: Cervical cancer cancers occupy third in the world after breast and lung cancer, because the symptoms did not appear at an early stage, thus referred to as the